2021
DOI: 10.1080/13880209.2021.1923757
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of allergic rhinitis treated by Centipeda minima from different geographic areas

Abstract: Context:The coriander plant Centipeda minima (L.) A. Braun et Aschers (Compositae) is used for the treatment of allergic rhinitis.Objective: Analyze the difference of the C. minima volatile oil from 7 geographic areas and its therapeutic effect on allergic rhinitis. Materials and methods: The volatile oils from different geographic areas were extracted and analyzed, the protein and biological pathway for the treatment of allergic rhinitis were predicted by network pharmacology. Established three groups of Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It has been used over the years to treat various diseases, including rheumatism, sinusitis, skin pruritus, and headaches (Figures 1(a) and 1(b) ) [ 18 ]. The Xanthii fructus has been shown to reduce mast cell-mediated allergy reactions [ 19 ], anti-inflammatory actions in lipopolysaccharide-stimulated inflammatory responses [ 20 ], and prevention of β -cell damage in type 1 diabetes [ 21 ].…”
Section: Xanthium Fructusmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used over the years to treat various diseases, including rheumatism, sinusitis, skin pruritus, and headaches (Figures 1(a) and 1(b) ) [ 18 ]. The Xanthii fructus has been shown to reduce mast cell-mediated allergy reactions [ 19 ], anti-inflammatory actions in lipopolysaccharide-stimulated inflammatory responses [ 20 ], and prevention of β -cell damage in type 1 diabetes [ 21 ].…”
Section: Xanthium Fructusmentioning
confidence: 99%
“…In a survey conducted by An et al, the anti-inflammatory role of XF has been reported on liposaccharide-stimulated mouse peritoneal macrophages [ 20 ]. Another study discovered that XF extract shields pancreatic β -cells from cytokine-induced damage by inhibiting nuclear factor kappa-B (NK- к B) [ 21 ]. Another study has established that XF is responsible for inhibiting chronic inflammation found in airways among bronchial asthma patients.…”
Section: Xanthium Fructusmentioning
confidence: 99%
“…Figure 6 shows that the active ingredient in A. ofcinarum binds to the core protein primarily carbonhydrogen bond, conventional hydrogen bond, van der Waals, and others. To compare the molecular docking results, we selected resveratrol, napabucasin, thalidomide, 5fuorouracil, bosutinib, celecoxib, ulixertinib, warfarin, and rosiglitazone as positive drugs with their corresponding proteins [40][41][42][43][44][45][46][47][48]. Te active ingredient binds to AKT1, STAT3, TNF, MAPK1, ALB, and PPARG were found to be more efective than the positive drug, while binding to TP53, SRC, and EGFR was found to be slightly weaker (Table 2).…”
Section: Results Of Molecular Dockingmentioning
confidence: 99%
“…It has been shown to possess anti-inflammatory and antioxidant properties [ 3 ]. Moreover, Centipeda minima (L.) essential oil is a multi-target agent and provides a new research platform and represents a reference for the treatment of allergic rhinitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%